Defense as a European public good: Delivery and financing - Roel Beetsma; Marco Buti; Francesco Nicoli (EconPol Forum, 2024)
We use data breaches of U.S. firms from 2005 to 2018 to examine the association between corporate communication and the likelihood of data breaches. We find that positive tone of annual reports (10-K filings) has a significant and positive association with the odds of a data breach. We further explore the related mechanisms and find strong evidence that the association between positive tone of annual reports and odds of a data breach is largely attributable to a firm's internal resources and market prospects (proxied by 'cash to total assets' and 'excess stock returns'). We also find that in the firms with more readable 10-K filings, positive tone is not associated with a higher likelihood of a data breach. This finding highlights the importance of communication tone and transparency in the context of potential data breaches.Defense qualifies as a quintessential European public good. It fulfills the standard properties of a public good, being non-excludable and nonrivalrous, and can provide considerable economies of scale and large positive spillovers. Despite the reluctance of a number of EU governments to share defense sovereignty, opinion polls suggest strong support for common EU policies, including defense policy. Maybe somewhat surprisingly, support for the latter is roughly equal for Europeans living in the eastern and western parts of the EU. Building a stronger EU involvement in defense should be based on the combination of delivery and financing at the national and EU level. These define genuine European public goods, where financing and delivery take place at the EU level, and other combinations, which define European public goods "by aggregation". While building a common defense policy will inevitably be a gradual endeavor, concrete steps via the implementation of new EU fiscal rules, the planning of a successor to Next Generation EU, and the preparation of the new multiannual financial framework should take place as a matter of urgency. An EU defense policy should operate within NATO, and EU defense policy decisions would then be subordinated to NATO decisions. As not all EU member states may be willing to join from the beginning, a practical way to go forward would be to form a coalition of the willing and start with those building blocks for which the added value is obvious (air and missile defense, integrated logistics, some procurement).
Keywords: 330